THM and HAA formation from NOM in raw and treated surface waters - Golea, Dan; Upton, Andrew; Jarvis, Peter; Judd, Simon J. (IWA Publishing, 2017)
The disinfection by-product (DBP) formation potential (FP) of natural organic matter (NOM) in surface water sources has been studied with reference to the key water quality determinants (WQDs) of UV absorption (UV254), colour, and dissolved organic carbon (DOC) concentration. The data set used encompassed raw and treated water sampled over a 30-month period from 30 water treatment works (WTWs) across Scotland, all employing conventional clarification. Both trihalomethane (THM) and haloacetic acid (HAA) FPs were considered. In addition to the standard bulk WQDs, the DOC content was fractionated and analysed for the hydrophobic (HPO) and hydrophilic (HPI) fractions. Results were quantified in terms of the yield (dDBPFP/dWQD) and the linear regression coefficient R2 of the yield trend. The NOM in the raw waters was found to comprise 30–84% (average 66%) of the more reactive HPO material, with this proportion falling to 18–63% (average 50%) in the treated water. Results suggested UV254 to be as good an indicator of DBPFP as DOC or HPO for the raw waters, with R2 values ranging from 0.79 to 0.82 for THMs and from 0.71 to 0.73 for HAAs for these three determinants. For treated waters the corresponding values were significantly lower at 0.52–0.67 and 0.46–0.47 respectively, reflecting the lower HPO concentration and thus UV254 absorption and commensurately reduced precision due to the limit of detection of the analytical instrument. It is concluded that fractionation offers little benefit in attempting to discern or predict chlorinated carbonaceous DBP yield for the waters across the geographical region studied. UV254 offered an adequate estimate of DBPFP based on a mean yield of ∼2600 and ∼2800 μg per cm−1 absorbance for THMFP for the raw and treated waters respectively and ∼3800 and2900 μg cm−1 for HAAFP, albeit with reduced precision for the treated waters.
Keywords: Trihalomethanes; Haloacetic acids; UV254; Dissolved organic carbon; Correlation coefficient